Value-based Design Decision on Building System Selection - Murti F; Utomo C (International Conference on Engineering and Technology Development (ICETD), 2017)
This paper presents a decision model for technical solution options on building system selection. There are many studies on design decision making using multicriteria, such as in assessment of exterior building wall system; selection of steel structure; structural alternatives of prefabricated concrete and metal clad; and roof system selection. The characteristic of value criteria has not been widely used to previous research. Existing models that are commonly accepted are optimization-based models, for example aggregation methods, but these are not able to solve the problem of value criteria on design decision. The model is based on a satisficing function/cost preferences. It is multi-attribute, and the environment is in a Value Management (VM) process. Since “value” is the main single objectives for the decision model of VM, the attributes for this decision model therefore is function and cost. This also provides the method to construct the Life Cycle Cost (LCC) analysis for the cost attributes and the Function Analysis System Technique (FAST) for the function attributes. This research applies the satisficing game method where function and cost of solution techniques for a building system is formulated and the reduction of the technical solutions based on function/cost preferences can be made. Therefore solving the problem on computerizing the creativity of human/decision participant helps to elaborate on every possibility of the technical solutions and reduce them before choosing the best solution